PENGARUH ALOKASI ANGGARAN PEMBANGUNAN INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI KABUPATEN BULUNGAN - Fitriyani, Nur; Sriekaningsih, Ana (JEB17 : Jurnal Ekonomi dan Bisnis, 2020)
This research aims to examine whether the budget allocation for infrastructure development has a significant effect on economic growth in the Bulungan district. To analyzes the relationship among dependent and independent variable under this study used simple linear regression method. Taken fromk the result of this study can be concluded that when budget allocation of infrastructure development is constant then the economic growth in the Bulungan district as 4,973 percent. Budget allocation of infrastructure development on Economic growth in the Bulungan district get rise, the Economic growth in the Bulungan district will be increase. And contribution of Budget allocation of infrastructure development variable on economic growth in the Bulungan district only 44,5 percent. Based on the result, then can be suggested to the Goverment of Bulungan District to intensifying strategic infrastructure budget such as infrastructure under agriculture sector, road and bridge infrastructure, able to open the isolation of each region which still experience obstacle in marketing their own crops. Beside enlarger the infrastucture development budget, it be expected that the goverment make controlling and supervision in detail on the determined budget so the infrastructure development budget be right on the target it be able to trigger the economic growth. Goverment of Bulungan District become more selective in positioning each structural officials in each stage of official position in order to have performance and loyalty to the leader and synergy in developing Bulungan district economy. Developing the potential of Bulungan District at present does not managed professionally like tourism sector, to adding goverment income source in turn it can be generate the economic growth. Keywords : infrastructure budget allocation, economic growth